Hubungan Antara Teknologi Informasi dan Keterampilan Karyawan dengan Kompetensi Administrasi Karyawan pada PDAM - Rifdah Amara Sari; Marsofiyati Marsofiyati (Politeknik Kampar, 2024)
This study examines the effects of information technology and employee performance on administrative skills at PDAM, which is crucial for providing aviation services that are affordable for the general public. According to the theory put forth by the ahli, information technology plays a crucial role in increasing administrative efficiency and effectiveness by improving data access, managing knowledge effectively, and facilitating communication. Using both quantitative and qualitative methods, data was collected from observers, questionnaires, and wawancara regarding 41 PDAM employees. The study's findings indicate that the kuesioner instrument has high validity and reliability (nilai above 0.70), indicating consistency in assessing administrative, technological, and instructional errors. The results of the regression analysis indicate that there is a significant positive correlation between technological use and administrative proficiency. This highlights the need of ongoing technological training in enhancing employee competency and productivity.